Picking up litter when walking outdoors: People engage in physical activity for planetary health - Stephanie Schoeppe; Emily Bryson; Rebecca Williams; Sally Symons; Tayla Hall (Sustainable Environment)
Litter accumulating in natural environments has led to plastic pollution on land, in waterways and in oceans. To address this problem, people have started to pick up litter when walking outdoors. However, research on this emerging pro-environmental behaviour is very limited. In the web-based Litter Walker Survey conducted in 2021/2022, we investigated Australian adults aged 18+ years (N = 547, mean age: 51 years, 86% female) who pick up litter when walking outdoors in terms of litter walking behaviour, motivations to start picking up litter, and individual and social factors associated with litter walking. Findings showed that most participants (80%) regularly engaged in litter walking (≥1–3 times per week). Participants were motivated by a sense of social responsibility, environmental consciousness and inspiration from others. Middle age (OR = 1.95, p = 0.034), physical activity motivation (OR = 2.85, p = 0.011) and previous participation in clean-up events (OR = 1.93, p = 0.019) were associated with regular litter walking. In conclusion, community-based initiatives to promote picking up litter during outdoor activities may benefit from targeting middle-aged adults and combining walking with collecting litter for planetary health. Community clean-up events may provide an avenue to inspire litter walking.